First Iranian record of the family Odiniidae (Diptera: Opomyzoidea), including two species new to the Middle East region - Parchami-Araghi, Mehrdad; Majnon-Jahromi, Bahareh; Gilasian, Ebrahim; Withers, Philip; Gaimari, Stephen D.; Fallahzadeh, Majid (Zootaxa, 2018)
The family Odiniidae is newly reported from Iran through the recent discovery of the species Odinia meijerei Collin, 1952 and Turanodinia graciosa Krivosheina & Krivosheina, 1996 in Iran and the Middle East region. The species T. graciosa is here elevated from the rank of subspecies (Turanodinia stackelbergi graciosa Krivosheina & Krivosheina, 1996) to species level. This taxonomical change was based on the comparison of the male genitalia of T. graciosa with T. stackelbergi Krivosheina & Krivosheina. Images of the habitus and male genitalia of O. meijerei and T. graciosa are provided.